PjBL and PjBL-STEM: Which model best enhances students’ creative thinking? - Andinawati Dwita Karina; Dwi Oetomo; Meti Indrowati (University of Muhammadiyah Malang, 2024)
In this century, humans are required to be able to adapt to the development of the times and are required to be able to answering and solving all problems that arise. One of the abilities that must be developed to face these challenges, namely the ability in the field of creativity. The research’s purpose is (1) to determine the differences in students' creative thinking abilities using the PjBL learning model and the PjBL-STEM learning model on class X environmental change material, (2) to determine students' responses to the PjBL-STEM learning model. This research used a posttest only control group design. The population used is class X1-X10 SMA Al Islam 1 Surakarta for the 2023/2024 academic year, a total of 384 students. The sampling technique used cluster random sampling, class X7 with 38 students as the control class using the project-based learning (PjBL) learning model and class X3 with 40 students as an experimental class using an integrated STEM with project-based learning (PjBL) learning model. Data collection was carried out using documentation, tests regarding creative thinking abilities, and student response questionnaires. The data analysis technique was carried out using a one-way t test. The research instruments are teaching modules, LKPD, creative thinking skills questions, and student response questionnaires. The instrument validation technique is carried out using validity tests and reliability tests. The results of the research show that (1) there is a significant difference in students' creative thinking abilities on environmental change material using the PjBL-STEM learning model, (2) students' responses to the PjBL-STEM learning model are included in the positive category.